THE INFLUENCE OF EMOTIONAL INTELLIGENCE LEVEL AND INDIVIDUAL CHARACTERISTICS ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR OF EMPLOYEES OF THE TRADE AND INDUSTRY SERVICE OF GOWA REGENCY - Arhan Tri Putra; Anwar Anwar; Rezky Amalia Hamka; Agung Widhi Kurniawan; Tenri Sayu Puspitaningsih Dipoatmodjo (Universitas Negeri Makassar, 2026)
Abstract: This study aims to analyze the influence of emotional intelligence and individual characteristics on Organizational Citizenship Behavior (OCB) among employees of the Gowa Regency Trade and Industry Department. This study uses a quantitative approach with an associative method. The study population consisted of 49 employees with a saturated sampling technique so that the entire population became respondents. Data were collected through questionnaires and analyzed using multiple linear regression. The results showed that partially emotional intelligence had a positive and significant effect on OCB with a calculated t value of 9.092 and a significance of <0.001. Conversely, individual characteristics did not have a significant effect on OCB with a calculated t value of 0.507 and a significance of 0.614. Simultaneously, emotional intelligence and individual characteristics had a significant effect on OCB with a calculated F value of 49.647 and a significance of <0.001. The coefficient of determination (R²) value of 0.683 indicates that 68.3% of the variation in OCB can be explained by these two variables, while 31.7% is influenced by other factors outside the study. These findings indicate that emotional intelligence is the most dominant factor in increasing employee OCB behavior.Keywords: Emotional Intelligence, Individual Characteristics, Organizational Citizenship Behavior